Magnetic Properties of Manganese-Iron Multi-Metal Cyanide Compound Ni1.15Mn0.35[Fe(CN)6]·6H2O - He, Yun; Ji, Zhimin; Lin, Qing; Huang, Haifu; Kong, Wenjie (Asian Journal of Chemistry, 2014)
A multi-metal prussian blue compound Ni1.15Mn0.35[Fe(CN)6]·6H2O has been synthesized. The IR spectrum of the compound shows two bands at 2096.42 and 2162.13 cm-1 indicating the existence of two types of cyanide groups.It undergoes a paramagnetic to ferromagnetic transition at 21 K. These results indicate that there exist a ferromagnetic exchange interaction in the complexes. According to Curie-Weiss law,paramagnetic Curie temperature (Q) is 13.81 K and the Curie-Weiss constant (C) is 2.21 cm3 K mol-1. In addition, the c’(T) and c’’ (T) show clear peak around 18-20 K. The behaviour of c’ and c’’ is typical of a spin glass state go through a maximum with strong frequency dependence. The observed value of coercive field (Hc) and remanent magnetization (Mr) for the compound are 1.72 KOe and 0.682 μb, respectively.